2000
DOI: 10.1073/pnas.97.16.9335
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of interepidemic periods of mosquito-borne disease

Abstract: Dengue viruses and malaria protozoa are of increasing global concern in public health. The diseases caused by these pathogens often show regular seasonal patterns in incidence because of the sensitivity of their mosquito vectors to climate. Between years in endemic areas, however, there can be further significant variation in case numbers for which public health systems are generally unprepared. There is an acute need for reliable predictions of within-year and between-year epidemic events. The prerequisite fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
148
0
8

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(170 citation statements)
references
References 48 publications
12
148
0
8
Order By: Relevance
“…This pattern of biennial epidemics more closely resembles the observed multi-annual cycle of dengue epidemics in endemic countries, including the pattern observed in Brazil (Nogueira et al 2007, Nogueira & Eppinghaus 2011. In agreement, other studies have shown the importance of the parameters related to the vector-host interaction, including the biting rate, in determining the seasonal and multi-annual cycle of dengue (Hay et al 2000, Bartley et al 2002. A more severe biennial epidemic implies that the virus, during the epidemic, is circulating among a greater proportion of the population, thus causing the number of secondary infections to increase.…”
Section: Mosquito Population Dynamicssupporting
confidence: 72%
“…This pattern of biennial epidemics more closely resembles the observed multi-annual cycle of dengue epidemics in endemic countries, including the pattern observed in Brazil (Nogueira et al 2007, Nogueira & Eppinghaus 2011. In agreement, other studies have shown the importance of the parameters related to the vector-host interaction, including the biting rate, in determining the seasonal and multi-annual cycle of dengue (Hay et al 2000, Bartley et al 2002. A more severe biennial epidemic implies that the virus, during the epidemic, is circulating among a greater proportion of the population, thus causing the number of secondary infections to increase.…”
Section: Mosquito Population Dynamicssupporting
confidence: 72%
“…Whatever the cause, the history of multiple epidemics in the earlier part of the century, including many at higher altitudes, makes it unnecessary to infer climate change as a contributory factor. Moreover, a set of wellmaintained meteorologic records shows no significant change in temperature over recent decades (103,128), and a retrospective study of 33 years of monthly incidence data from the Brookebond tea-growing estates did not reveal any relationship between climate variables and the timing or duration of interepidemic periods (130). Indeed, in a detailed report to WHO (131), a group of malaria specialists based in Nairobi dismissed those who claim a global warming link as "scientific Nostradamuses.…”
Section: Malaria In the Tropicsmentioning
confidence: 99%
“…Immunologic history, expressed as the herd immunity, is presumably the dominant factor. Moreover, a retrospective analysis of 33 years of monthly data on DHF incidence in Bangkok, Thailand, did not reveal any relationship between climate variables and the timing of epidemics (130).…”
Section: Tropics and Subtropicsmentioning
confidence: 99%
“…For this reason, a second malaria time series at an adjacent plantation was also considered (this has already been the subject of previous studies, e.g. Hay et al 2000), as a basis for comparison and discussion (figure S5 in the electronic supplementary material). We refer to this time series as BBK, for Brooke Bond Farms.…”
Section: Rainfall and Malaria Datamentioning
confidence: 99%